Coral smuggling (factors, effects, and mechanisms to combat it) - KERRAS, Rahma; MOHAMED KARIM, Feriha (Social Sciences Journal)
This present study is aiming atcloselyidentifying the subject of sumggling of coralsthis has been possible through rhéprésentation of différent concepts of smuggling, also. The vocable of corrals, and to highlight the main factors pushing the individual to adopt this criminal behavoir, and what follows as different harmful consequences. Finally, this study is deoling with different ways of combating this phenomenon, either from algerian internal perspective, or from external perspective through Arab cooperation to eliminate partially this phenomenon